2020
DOI: 10.18632/aging.103998
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced p53 drives BAG5 cochaperone expression to control α-synuclein aggregation in Parkinson's disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder with the pathological hallmark of α-synuclein aggregation. Dysregulation of α-synuclein homeostasis caused by aging, genetic, and environmental factors underlies the pathogenesis of PD. While chaperones are essential for proteostasis, whether modulation of cochaperones may participate in PD formation has not been fully characterized. Here, we assessed the expression of several HSP70- and HSP90-related factors under various stresses and found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Chaperone and cochaperone systems are essential for protein folding or refolding and degradation of aggregated protein; thus, they prevent the cytotoxicity caused by aberrant protein accumulation [ 111 , 112 ]. p53 regulates the functional activity of HSP70 and HSP90 chaperone and cochaperone systems in neurodegenerative conditions [ 67 , 113 ]. Studies in PD cellular and animal models have shown that p53 activation increases the aggregation of α -synuclein in vulnerable neurons through inhibiting HSP70-mediated protein folding activity, accompanied by BAG5 protein overexpression [ 113 ].…”
Section: P53 With Autophagy and Protein Aggregationmentioning
confidence: 99%
See 3 more Smart Citations
“…Chaperone and cochaperone systems are essential for protein folding or refolding and degradation of aggregated protein; thus, they prevent the cytotoxicity caused by aberrant protein accumulation [ 111 , 112 ]. p53 regulates the functional activity of HSP70 and HSP90 chaperone and cochaperone systems in neurodegenerative conditions [ 67 , 113 ]. Studies in PD cellular and animal models have shown that p53 activation increases the aggregation of α -synuclein in vulnerable neurons through inhibiting HSP70-mediated protein folding activity, accompanied by BAG5 protein overexpression [ 113 ].…”
Section: P53 With Autophagy and Protein Aggregationmentioning
confidence: 99%
“…p53 regulates the functional activity of HSP70 and HSP90 chaperone and cochaperone systems in neurodegenerative conditions [ 67 , 113 ]. Studies in PD cellular and animal models have shown that p53 activation increases the aggregation of α -synuclein in vulnerable neurons through inhibiting HSP70-mediated protein folding activity, accompanied by BAG5 protein overexpression [ 113 ]. BAG5 is an important stress-induced backup nucleotide exchange factor of HSP70 associated with the protein activation.…”
Section: P53 With Autophagy and Protein Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…Astonishingly, some studies have reported that BAG5 interaction with other chaperones might interfere with their E3 ubiquitin ligase activity such that it might cause accumulation of toxic oligomers of α-synuclein (α-syn) ( Chen et al, 2020 ). Parkinson’s disease is a neurodegenerative disorder characterized by abnormal protein homeostasis causing accumulation of the protein α-syn in the form of Lewy bodies ( Orme et al, 2018 ; Goldman et al, 2020 ).…”
Section: Role Of Bag5 In Parkinson’s Diseasementioning
confidence: 99%